Characteristics of Carrageenan Extracted from Commercially Important Seaweeds from the MIMAROPA Region, Philippines: Characteristics of Carrageenan from Seaweeds - Joan E. Abel; Tolentino, Precious Dee (Fishery Technology, 2024)
This study analyzed the physicochemical attributes of raw dried seaweed samples (Eucheuma striatum, Kappaphycus alvarezii and Eucheuma denticulatum) obtained from different seaweed culture sites in the MIMAROPA Region. The results showed that the moisture content ranged from 35.70% to 38.67%, ash content from 16.22% to 18.55%, impurities from 1.42% to 1.59%, and CAW (clean anhydrous seaweed) from 40.40% to 50.03%. All parameters tested met the local and international standards for dried seaweeds. The samples underwent an alkali extraction process to obtain Philippine natural grade (PNG) carrageenan. The physicochemical attributes analyzed included yield (35.36% to 47.96%), moisture (15.38% to 16.99%), insoluble ash (0.96%), and sulfate content (27.45% to 37.33%). The factors such as yield, insoluble ash, and sulfate content were consistent with previous studies. However, the moisture content did not meet the required level, which is an important parameter for dry additives like carrageenan. The rheological properties of the extracted carrageenan from the three samples were assessed, including gel strength (205 g/cm2 to 320.22 g/cm2), gel viscosity (12.54 Cps to 13.59 Cps), gelling point (18.59oC to 23.57oC), and melting point (47.15oC to 60.25oC). Except for the gel strength, all other parameters met the standards for carrageenan. Overall, the physicochemical attributes and rheological properties of the carrageenan extracted from the analyzed seaweed samples were mostly compliant with the established standards, highlighting their potential for various applications in the food and pharmaceutical industries.